2022
DOI: 10.1038/s41598-022-22245-6
|View full text |Cite
|
Sign up to set email alerts
|

Attention neuroenhancement through tDCS or neurofeedback: a randomized, single-blind, controlled trial

Abstract: Neurofeedback and transcranial Direct Current Stimulation (tDCS) are promising techniques for neuroenhancement of attentional performance. As far as we know no study compared both techniques on attentional performance in healthy participants. We compared tDCS and neurofeedback in a randomized, single-blind, controlled experiment assessing both behavioral (accuracy and time reaction) and electrophysiological (N1, P1, and P3 components) data of participants responding to the Attention Network Task (ANT). Eighty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Moezzi et al (2021) found that tDCS over the left Dorsolateral Prefrontal Cortex (DLPFC) for five consecutive days improved attentional control in healthy individuals, as measured by an increase in P600 amplitudes and a decrease in reaction time in an Integrated Visual and Auditory-Adult Edition (IVA-AE) Task (Moezzi et al, 2021). A study by Rêgo et al (2022) found similar results. tDCS over the left DLPFC improved sustained attention in healthy individuals.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moezzi et al (2021) found that tDCS over the left Dorsolateral Prefrontal Cortex (DLPFC) for five consecutive days improved attentional control in healthy individuals, as measured by an increase in P600 amplitudes and a decrease in reaction time in an Integrated Visual and Auditory-Adult Edition (IVA-AE) Task (Moezzi et al, 2021). A study by Rêgo et al (2022) found similar results. tDCS over the left DLPFC improved sustained attention in healthy individuals.…”
Section: Introductionmentioning
confidence: 82%
“…tDCS over the left DLPFC improved sustained attention in healthy individuals. The results showed that tDCS over the left DLPFC enhanced reaction and P2 amplitudes in a visual flanker task, indicating an improvement in sustained attention after the stimulation ( Rêgo et al, 2022 ). Moreover, tDCS has been shown to have beneficial effects on stress-related cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to allowing for an intense and original creative experience, the system also allows for the collection of data on implicit learning and the interplay between conscious and unconscious processes. Finally, it could be used as a tool to increase attentional focus [ 1 ], to support learning processes [ 4 ], and as a creative warm-up [ 5 , 7 ].…”
Section: Discussion Conclusion and Future Directionsmentioning
confidence: 99%
“…Another possible use of a BCI is in neurofeedback, which is the modulation of cerebral activity during a task based on certain feedback about the ongoing EEG. It can be used, for example, to improve focal attention [ 1 ], working memory [ 2 ], emotional management [ 3 ], learning [ 4 ], and creative thinking [ 5 ] in both experimental and real-life contexts. In addition, multiple settings can be implemented.…”
Section: Introductionmentioning
confidence: 99%